NuSTAR Observations of GS 1826-238 in the Extended Soft State - B. W. Grefenstette; M. C. Brumback; D. J. K. Buisson; R. M. Ludlam; G Mastroserio; S. N. Pike; J. A. Tomsick; S. B. Yun (The Astrophysical Journal, 2025)
We report on the first focused NuSTAR observations of the neutron star low mass X-ray binary GS 1826-238, the “Clocked Burster,” since the extended soft state began in 2014. Throughout this day-long observation, we see spectral variability that is consistent with the “banana” branch of atoll LMXBs. The NuSTAR hard X-ray spectrum is consistent with that seen during the initial soft-state excursion in 2014 and is modeled as a double Comptonized plasma: one with low temperature and high optical depth, the other with high temperature and low optical depth. The spectral variations that we see in this source are mostly consistent with variations in the optical depth of the hot component, though the total flux from the source remains nearly constant. A single Type I X-ray burst is seen during this observation, which has a short main peak (timescales of seconds) followed by an extended tail of emission. The shape of this burst is not consistent with a PRE and provide diagnostic information on the regions of the NS surface supplying the fuel for the thermonuclear reaction.